„W obronie życia nienarodzonych”. Głos Kościoła i środowisk katolickich w debacie okołoaborcyjnej w okresie Wielkiej Nowenny (1956–1966) - Jarkiewicz, Katarzyna (Pamięć i Sprawiedliwość, 2017)
The Church and the Catholic community during the Great Novena (1956–1966) contested the liberal abortion laws introduced by the Communists, arguing that it led to the depopulation of Poland. Formed of pronatalist attitudes based on the experiences of the previous epoch: Catholic parish counseling was developed, spouses were trained on natural family planning methods. Poles were integrated around the Millenium program proclamation of Card. Wyszyński, in which conscience of women through prayer, pilgrimage and preaching. Particular attention has been paid to single mothers and to large families, offering them social and organizational assistance in their parenting. The program of reception of church teaching in the field of marriage and the family was transferred to the forum of the council debate, actively developing the content of the document “Humanae vitae”. In this regard, the effect of the Church and the Catholic community was to strengthen the image of Poland as a country in which it struggled in defense of life and effectively countered the government’s reproductive policy.